Dental caries prevalence in children during temporary protective care according to type of abuse - Yuki Nakamura; Yukiko Nogami; Yoko Iwase; Mio Hozawa; Tetsuya Sotome; Issei Saitoh; Akitsugu Ohuchi; Haruaki Hayasaki (BMC, 2024)
Abstract Background This study investigated the correlation between the prevalence of dental caries and the presence and type of abuse. Methods Participants were 534 children admitted for care at two child guidance centers (CGCs) in Niigata, Japan. Data pertaining to abuse, including the reason for temporary protective care and the type of abuse, and the oral examination results of the children, were collected. These results were then compared with those of a national survey and analyzed in relation to the presence and type of abuse. Results The odds ratio for decayed teeth was 4.1, indicating a higher risk in children admitted to the CGCs. However, no significant association was found between the presence of decayed, filled, or caries-experienced teeth and the presence of abuse. A significant positive association was observed between dental caries and one type of abuse, indicating a greater prevalence of dental caries in cases of neglect. The findings of this study suggest that the type of abuse, rather than its presence, is associated with dental caries. Conclusions Our findings suggest that proactive support should be provided to children in problematic nurturing environments, regardless of whether they have been subjected to abuse.